Treatment provision and management for the menopause: a multinational survey study - Martin-Key, Nayra A.; Funnell, Erin L.; Bahn, Sabine (Frontiers in Global Women's Health, 2025)
IntroductionDespite available safe hormonal and non-hormonal interventions, most women with troublesome menopausal symptoms do not receive effective, evidence-based therapy, with notable international disparities in provision. This study aimed to investigate self-reported menopausal care experiences in a self-selecting sample from five English-speaking countries: Australia, Canada, New Zealand, the United Kingdom, and the United States, through an anonymous online survey.MethodsThe 15–20 min survey, delivered via Qualtrics XM®, included questions on sociodemographic characteristics and treatment experiences, such as the number of healthcare professionals (HCP) seen before getting a prescription, ease of obtaining treatment, involvement in treatment discussions, appropriateness of treatment review and optimization, side effect tolerability, and overall satisfaction.ResultsData from 3,062 respondents were analyzed: Australia (16.59%, n = 508), Canada (17.54%, n = 537), New Zealand (16.59%, n = 508), UK (24.00%, n = 735), and US (25.28%, n = 774). Significant international differences were observed in both healthcare access and prescribing patterns. More women in the UK and US consulted an HCP compared with Australia, Canada, and New Zealand [χ²(4, N = 3062) = 101.02, p < 0.001, φc = 0.18]. Prescription rates were higher in New Zealand, the UK, and the US compared with Australia and Canada [χ²(4, N = 2,485) = 75.71, p < 0.001, φc = 0.18]. However, UK respondents, despite longer treatment use, generally reported less involvement in treatment discussions, poorer treatment review, lower side effect tolerability, and reduced satisfaction compared with other countries across treatment types.DiscussionBased on a self-selected cohort, these findings reveal critical gaps in menopause care, including disparities in treatment access and international differences in patient involvement. Greater access to healthcare in the UK and the US did not translate into higher satisfaction, highlighting the need for patient-centered approaches. Improving care requires better clinician education and strategies to enhance communication and shared decision-making.